2019
DOI: 10.1016/j.nicl.2019.101736
|View full text |Cite
|
Sign up to set email alerts
|

pH-weighted molecular MRI in human traumatic brain injury (TBI) using amine proton chemical exchange saturation transfer echoplanar imaging (CEST EPI)

Abstract: Cerebral acidosis is a consequence of secondary injury mechanisms following traumatic brain injury (TBI), including excitotoxicity and ischemia, with potentially significant clinical implications. However, there remains an unmet clinical need for technology for non-invasive, high resolution pH imaging of human TBI for studying metabolic changes following injury. The current study examined 17 patients with TBI and 20 healthy controls using amine chemical exchange saturation transfer echoplanar imaging (CEST EPI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 63 publications
(73 reference statements)
1
22
0
Order By: Relevance
“…A previous approach of Zhu et al 25 at 3T enabled a FOV = 212 × 212 × 132 mm 3 at (2.2 mm) 2 in‐plane resolution in 20 s per presaturation offset. A more recent 2D‐EPI–based study of Ellingson et al 26 reported (2 mm) 2 in‐plane resolution with FOV = 256 × 256 × 100 mm 3 in approximately 14 s per presaturation offset, also at B 0 = 3T. Krishnamoorthy et al 27 had chosen a FLASH approach with two shots per readout volume at B 0 = 7T.…”
Section: Discussionmentioning
confidence: 99%
“…A previous approach of Zhu et al 25 at 3T enabled a FOV = 212 × 212 × 132 mm 3 at (2.2 mm) 2 in‐plane resolution in 20 s per presaturation offset. A more recent 2D‐EPI–based study of Ellingson et al 26 reported (2 mm) 2 in‐plane resolution with FOV = 256 × 256 × 100 mm 3 in approximately 14 s per presaturation offset, also at B 0 = 3T. Krishnamoorthy et al 27 had chosen a FLASH approach with two shots per readout volume at B 0 = 7T.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown that brain acidosis severity is a strong predictor of long-term functional outcome (Clausen et al, 2005;Ellingson et al, 2019). To that end, we performed a battery of behavioral tests and histopathological examination to determine the chronic impact of acute brain acidosis on recovery (see Figure S4).…”
Section: Depletion Of Hv1 Limits Neurodegeneration After Tbi and Immentioning
confidence: 99%
“…Although brain tissue acidosis has long been recognized as an important pathological feature of TBI, little is known regarding the cellular and molecular mechanisms involved. Based upon correlational clinical studies, lactic acidosis was implicated as a key mechanism, as brain lactate concentrations are inversely correlated with brain pH after head injury and appear to reliably predict both short-term and long-term clinical outcomes (Clausen et al, 2005;Ellingson et al, 2019;Gupta et al, 2004;Rehncrona, 1985). But the current understanding of TBI-induced acidosis and its underlying mechanisms is limited.…”
Section: Introductionmentioning
confidence: 99%
“…As rapidly emerging technologies, including new imaging sequences and higher resolution scanners, allow for new visualizations, imaging biomarkers are increasingly promising. 98 Patients with TBI often face prolonged emergency room visits and are particularly susceptible to motion artifacts that may render images unreadable. More advanced diffusion MRI techniques that use multishell sampling and biophysical modeling can separate these features.…”
Section: Biomarker Acquisition and Quantificationmentioning
confidence: 99%
“…These methods include susceptibility-weighted imaging and derived quantitative susceptibility mapping that have been utilized to characterize diffuse axonal injury and identify chronic hemosiderosis better than existing sequences 96 ; magnetic transfer ratio imaging, which has been shown to decrease in association with axonal injury 97 ; and chemical exchange saturation transfer echoplanar imaging, which was recently shown to successfully identify tissue at risk for chronic injury due to cerebral acidosis in a clinical setting. 98 Patients with TBI often face prolonged emergency room visits and are particularly susceptible to motion artifacts that may render images unreadable. New preprocessing tools may compensate for this loss of data.…”
Section: Biomarker Acquisition and Quantificationmentioning
confidence: 99%